PENGEMBANGAN TRAINER ELEKTRONIKA DIGITAL PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA KELAS X TAV DI SMK NEGERI 1 PERCUT SEI TUAN - Delani, Desta; Junaidi, Agus (JEVTE Journal of Electrical Vocational Teacher Education, 2023)
Abstract This study aims to: (1) Design a digital electronics trainer along with a jobsheet on basic electrical and electronics subjects for class X students of Audio Video Engineering skill competency at SMK Negeri 1 Percut Sei Tuan; (2) Knowing the level of feasibility of digital electronics trainers in basic electrical and electronics subjects for class X students of Audio Video Engineering competency skills at SMK Negeri 1 Percut Sei Tuan; (3) Produce digital electronics trainers who can meet the requirements in basic electrical and electronics subjects for class X students of Audio Video Engineering skill competency at SMK Negeri 1 Percut Sei Tuan.            The result of the research is a Digital Electronics Trainer consisting of a fiber PCB board, LED, Male Header, 220 resistor, a series of logic gates equipped with each IC, and using a Dip Switch. The results of the trainer requirements validation test by material experts amounted to 92.5% with the category of highly qualified; and the results of the validation test by experts obtained a score of 83.125% with a very decent category; User trials of 92.125% with a very decent category. Based on all the results of the study, it was concluded that the Digital Electronics Trainer was very suitable to be used as a learning medium for class X TAV at SMK Negeri 1 Percut Sei Tuan. Key Words: Digital Electronics, Development, Trainer AbstrakPenelitian ini bertujuan untuk : (1) Merancang trainer elektronika digital beserta jobsheet pada mata pelajaran dasar listrik dan elektronika untuk siswa  kelas X kompetensi keahlian Teknik Audio Vidio di SMK Negeri 1 Percut Sei Tuan; (2) Mengetahui tingkat kelayakan trainer elektronika digital pada mata pelajaran dasar listrik dan elektronika untuk siswa  kelas X kompetensi keahlian Teknik Audio Vidio di SMK Negeri 1 Percut Sei Tuan; (3) Menghasilkan trainer elektronika digital yang dapat memenuhi persyaratan pada mata pelajaran dasar listrik dan elektronika untuk siswa kelas X kompetensi keahlian Teknik Audio Video  di SMK Negeri 1 Percut Sei Tuan.     Hasil penetian adalah Trainer Elektronika Digital yang terdiri dari papan PCB fiber, LED, Header Male, Resistor 220 ????, rangkaian gerbang – gerbang logika dilengkapi masing – masing IC nya, dan menggunakan Dip Switch. Hasil uji validasi persyaratan trainer oleh ahli materi sebesar 92,5 % dengan kategori sangat memenuhi syarat; serta hasil uji validasi oleh para ahli diperoleh skor 83,125 % dengan kategori sangat layak; Uji coba pemakaian oleh user sebesar 92,125 % dengan kategori sangat layak. Berdasarkan seluruh hasil penelitian disimpulkan bahwa Trainer Elektronika Digital sangat layak digunakan sebagai media pembelajaran untuk kelas X TAV di SMK Negeri 1 Percut Sei Tuan..Kata Kunci: Elektronika Digital, Pengembangan, Trainer